CENTRAL POST-STROKE PAIN - Kania Aviandi Savitri (Journal of Pain, Headache and Vertigo, 2024)
Central post-stroke pain (CPSP) is a severe neuropathic pain condition that arises due to direct cerebrovascular lesions affecting the central somatosensory system. It significantly impacts patients' quality of life, disrupting their ability to perform daily activities and maintain social interactions. Despite advancements in stroke treatment, CPSP remains a challenge due to its persistent nature and often inadequate management. CPSP is prevalent among stroke survivors and often underdiagnosed due to its varied and subjective pain characteristics. The diagnosis of CPSP requires careful clinical evaluation and neuroimaging to exclude other pain causes. A multidisciplinary approach combining pharmacological treatments, non-pharmacological therapies and physical therapy is recommended. This review provides an overview of CPSP, including its definition, epidemiology, risk factors, clinical presentation, diagnostic criteria, and treatment options.